Auditory central pathways in children and adolescents with multiple sclerosis - Barbosa, Dayane Aparecida Nascimento; Silva, Liliane Aparecida Fagundes; Samelli, Alessandra Giannella; da Paz, José Albino; Matas, Carla Gentile (Arquivos de Neuro-Psiquiatria, 2023)
Background Multiple sclerosis (MS) is an inflammatory demyelinating disease. Auditory evoked potential studies have demonstrated conduction and neural processing deficits in adults with MS, but little is known about the electrophysiological responses in children and adolescents.Objective to evaluate the central auditory pathway with brainstem auditory evoked potentials (BAEP) and long-latency auditory evoked potentials (LLAEP) in children and adolescents with MS.Methods The study comprised 17 individuals with MS, of both sexes, aged 9 to 18 years, and 17 healthy volunteers, matched for age and sex. All individuals had normal hearing and no middle ear impairments. They were assessed with click-BAEP and LLAEP through oddball paradigm and tone-burst stimuli.Results Abnormal responses were observed in 60% of electrophysiologic assessments of individuals with MS. In BAEP, 58.82% of MS patients had abnormal responses, with longer wave V latency and therefore longer III-V and I-V interpeak latencies than healthy volunteers. In LLAEP, 52.94% of MS patients had abnormal responses. Although statistical differences were found only in P2-N2 amplitude, MS patients had longer latencies and smaller amplitudes than healthy volunteers in all components.Conclusion Children and adolescents with MS had abnormal BAEP responses, with delayed neural conduction between the cochlear nucleus and the lateral lemniscus. Also, abnormal LLAEP results suggest a decrease in neural processing speed and auditory sensory discrimination response.
Keywords: Multiple Sclerosis; Hearing; Electrophysiology; Evoked Potentials, Auditory; Central Nervous System